Ultrasonic time-of-flight measurements for inline gas analysis and process monitoring in the phenolic urethane cold box process - J. Sablowski; M. T. Asghar; M. S. Khan; M. Szucki; C. Kupsch (Journal of Sensors and Sensor Systems)
The phenolic urethane cold box (PUCB) process is widely employed for sand core production in the foundry industry. It allows high production rates of sand cores, which are later used for producing complex metal castings. The process begins by shooting a sand–binder mixture into a core box to define the core geometry. During the subsequent curing stage, catalysts are introduced to harden the binders and are then removed by blowing dry compressed air through the sand core. In order to optimize this complex and highly dynamic production process for efficiency and core quality, there is a need for measurement systems that can reliably monitor the curing stage.